A New Perspective on Growth of GaN from the Basic Ammonothermal Regime - Meißner, Elke; Jockel, Dietmar; Koch, Martina; Niewa, Rainer (Ammonothermal Synthesis and Crystal Growth of Nitrides, 2021)
Although the crystal growth of GaN under ammonothermal conditions is being performed for quite some years now, the physical processes going on in the autoclave are still debated. Insight in the autoclave by in situ techniques is difficult and numerical simulations are based on physical models where the experimental prove is eventually vague. This chapter reports a period of experimental work leading to a new vision of the basic ammonothermal process. We shortly summarize the 3D thermal- and transport model and a first chemical model. Subsequently, we propose an alternative picture for the ammonobasic crystal growth of GaN, which not only leads to consequences with regard to required pressures and temperatures but also to a potential new growth process. The proposed hypothesis and empirical model involves the presence of a liquid phase in the autoclave in form of an amidogallate complex.
CRIS-Team Scopus Importer:2021-03-05